Fabrication of ZIF-8/Cellulose Acetate Mixed Matrix Membrane for CO2/CH4 Separation - Tan, Xun (Universiti Teknologi PETRONAS, 2016)
With the drastic change of global warming attributed by the emission of CO2, removal of CO2 has become very important in the sweetening process of natural gas. Development of membrane technology has been advantageous towards the applications in gas separation. This research aims to synthesize ZIF-8 nano-crystals and fabricate a series of mixed matrix membranes (MMMs) by incorporating different loadings of ZIF-8 nano-fillers into cellulose acetate (CA) polymer matrix. The effect of different loading (5wt%, 10wt%, 15wt% and 20wt%) of ZIF-8 in MMM towards the CO2/CH4 gas separation was tested with pure gas permeation test. The optimum loading of ZIF-8 in MMM which resulted the best CO2/CH4 separation performance was 5wt% of ZIF-8 loading. Results showed that permeability of CO2 and CH4 increased from 12.19 barrer and 2.16 barrer in pure CA membrane to 245.75 barrer and 4.65 barrer in the MMM loaded with 5wt% of ZIF-8. The CO2/CH4 selectivity of ZIF-8/CA MMM reached up to 52.85 barrer from 5.63 barrer in pure CA membrane.